The Analysis of Humor in the Movie Script Entitled "How I Met Your Mother " by Using Hyme's Model os S-P-E-A-K-I-N-G and Conversational Implicature - Anak Agung Gede Yudha Paramartha (Lingua Scientia, 2011)
This study aims at analyzing the humors in the movie script entitled “How I Met Your Mother” by using Hymes’s Model of S-P-E-A-K-I-N-G and conversational implicature. The findings show that all of the implicatures are caused by the maxims which are broken, which are five maxims of relation, three maxims of quantity, two maxims of quality and two maxims of manner. Maxim of relation is the most appearing maxim and other two maxims; maxim of quantity and maxim of manner just take a small part of the conversation. While for the analysis of S-P-E-A-K-I-N-G model, the aspects which appear in the conversations are Setting and Scene (three appearances), Participants (two appearances), Ends (five appearances), Keys (four appearances) and Genre (two appearances). Act sequences and Norms do not appear at all, while Ends appears in all of the conversations. It is because the focus of this research is on the implied meaning that can promote humor.